1983
DOI: 10.1111/j.1526-4610.1983.hed2302059.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin ‐ E 2 Levels in the Saliva of Common Migrainous Women

Abstract: SYNOPSIS Prostaglandin E2 (PG‐E2) levels were measured in the saliva of 6 women suffering from common migraine, during an attack, and in the interval between attacks; the results obtained were compared to the levels found in a matched control group of healthy women. There was a significant increase in the levels of PG‐E2 during migraine attack P<0.05. These results may suggest that PG‐E2 takes an important role in the mechanism of migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

1985
1985
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 7 publications
(18 reference statements)
3
12
0
1
Order By: Relevance
“…The increase observed in PGE 2 during migraine attacks matches similar experience with this eicosanoid in migraine. 17 In relation to TXA 2 , our results are in the same order of magnitude as those obtained in the plasma of migraine patients. 18 No data were found on TXA 2 levels in saliva.…”
Section: Resultssupporting
confidence: 83%
“…The increase observed in PGE 2 during migraine attacks matches similar experience with this eicosanoid in migraine. 17 In relation to TXA 2 , our results are in the same order of magnitude as those obtained in the plasma of migraine patients. 18 No data were found on TXA 2 levels in saliva.…”
Section: Resultssupporting
confidence: 83%
“…The present study indicated that nasal lavage and saliva levels of LTB 4 were significantly lower and PGE 2 and TXB 2 levels did not differ significantly in migraineurs and controls during the headache‐free interval. Similar results were observed by Vardi et al who demonstrated that PGE 2 levels in the saliva of migraineurs were not significantly different from the controls 16 . However, another study showed lower levels of PGE 2 in migraineurs compared with controls 12 .…”
Section: Commentssupporting
confidence: 88%
“…However, future studies are needed to investigate whether the peripheral level of inflammatory mediators could be an indicator of an impending migraine attack. It has been demonstrated that the presence of inflammatory mediators such as prostaglandins and leukotrienes in plasma as well as in saliva during the migraine attack play a trigger role in migraine 11,12,16,21 …”
Section: Commentsmentioning
confidence: 99%
“…In 1983, Vardi et al 11 sought the presence of PGE 2 in the saliva of women suffering from common migraine and in that of controls. In 1981, Amroyan 9 studied migraine patients between attacks and during attacks and found PGE 2 levels three times and six times higher, respectively, than those in controls.…”
Section: Introductionmentioning
confidence: 99%